Introduction to forensic anthropology - Byers, Steven N. (Routledge, Taylor & Francis Group, 2017)
This book provides comprehensive coverage of the methods and issues in the current practice of forensic anthropology. It introduces students to all the major topics in the field, with material ranging from the attribution of ancestry and sex, to various forms of bone trauma, to identification through radiography. Introduction to Forensic Anthropology uses the terminology and best practices recommended by the Scientific Working Group for Forensic Anthropology (SWGANTH). The fifth edition has been fully updated in light of recent developments, incorporating new and improved methods as well as fresh data. The section on human osteology and odontology in particular has been expanded. This accessible and engaging text offers an array of features to support teaching and learning, including boxed case studies, extensive figures and, photographs, chapter summaries and student exercises, a glossary of terms, further resources via a companion website.